The complete works of Yuri Norstein - Norstein, Yuri ([s.l.] : Films by Jove, 2005)
25TH - THE FIRST DAY (1968) / co-réalisé par Y. Norstein et Arkadi Tyurun (10 min) ## THE BATTLE OF KERJENETS (1971) / co-réalisé par Y. Norstein et Ivan Ivanov-Vano (10 min) ## FOX AND RABBIT (1973) / réalisation et animation, Y. Norstein (12 min) ## HERON AND CRANE (1974) / réalisation, Y. Norstein ; scénario, R. Kachanov et Y. Norstein ; narration, Enokenti Smoktunovsky (10 min) ## HEDGEHOG IN THE FOG (1975) / réalisation et animation, Y. Norstein (10 min) ## TALE OF TALES (1978) / réalisation et animation, Y. Norstein (29 min).
In Russian with English subtitles.
film
Keywords: Norstein, Yuri